Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Evaluate the functions for the given input values.
f(x) = x² + 1
g(x) = 2f(x)
g(-3) =
g(2) =
g(7) =


Sagot :

Answer:

g(-3) = 20

g(2) = 10

g(7) = 100

Step-by-step explanation:

g(x) = 2f(x) tells us that g(x) is two times f(x). Instead of f(x) we can write (x² + 1).

g(x) = 2f(x)

g(x) = 2(x² + 1)

Multiply.

g(x) = 2x² + 2

Now that we have g(x) we just substitute values in the function.

g(-3) = 2(-3)² + 2

        = 2(9) + 2

        = 18 + 2  

        = 20

g(2) = 2(2)² + 2

        = 2(4) + 2

        = 8 + 2  

        = 10

g(7) = 2(7)² + 2

        = 2(49) + 2

        = 98 + 2  

        = 100

We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.